2007
DOI: 10.1063/1.2722271
|View full text |Cite
|
Sign up to set email alerts
|

Variational approach for the quantum Zakharov system

Abstract: The quantum Zakharov system is described in terms of a Lagrangian formalism. A time-dependent Gaussian trial function approach for the envelope electric field and the low-frequency part of the density fluctuation leads to a coupled, nonlinear system of ordinary differential equations. In the semiclassic case, linear stability analysis of this dynamical system shows a destabilizing rôle played by quantum effects. Arbitrary value of the quantum effects are also considered, yielding the ultimate destruction of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 29 publications
1
38
0
Order By: Relevance
“…However, the system can be decoupled in the adiabatic as well as semiclassical limit [2,6], where the solitons can be found to be more stable than in fully degenerate cases [6]. Other recent developments on the QZEs can be found in the literature [3][4][5][6][7][9][10][11]. Marklund [3] studied the kinetic theory of LWs interacting with quantum ionacoustic waves (QIAWs), where it was shown that the combined effects of partial coherence and quantum correction tend to enhance the modulational instability (MI) growth rate [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the system can be decoupled in the adiabatic as well as semiclassical limit [2,6], where the solitons can be found to be more stable than in fully degenerate cases [6]. Other recent developments on the QZEs can be found in the literature [3][4][5][6][7][9][10][11]. Marklund [3] studied the kinetic theory of LWs interacting with quantum ionacoustic waves (QIAWs), where it was shown that the combined effects of partial coherence and quantum correction tend to enhance the modulational instability (MI) growth rate [3].…”
Section: Introductionmentioning
confidence: 99%
“…Marklund [3] studied the kinetic theory of LWs interacting with quantum ionacoustic waves (QIAWs), where it was shown that the combined effects of partial coherence and quantum correction tend to enhance the modulational instability (MI) growth rate [3]. The temporal dynamics of the QZEs has been studied by Haas by means of a variational approach [4]. It has been found that the quantum coupling parameter plays a destabilizing role on localized structures, or Langmuir wave packets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some astrophysical compact objects, such as white dwarf or neutron stars, possess very high temperature but strong quantum effects as well due to their large densities (∼ 10 6 g/cm 3 ) [6]. There has been recent studies in quantum plasmas involving quantum turbulence [7], quantum analogues for the Harris sheet [8], quantum models taking into account spin [9,10], stable solitary structures [11], dark soliton and vortices solutions [12], variational structures for the quantum Zakharov system [13] as well as application of quantum hydrodynamic equations for carbon nanotubes [14].…”
Section: Introductionmentioning
confidence: 99%
“…Hass [23], Misra and Samanta [24], Mistra et al [25] etc. However, these investigations are based on the electron equation of state valid for the nonrelativistic limit.…”
Section: Introductionmentioning
confidence: 99%